Dampak Pandemi Covid-19 Terhadap Proses Pembelajaran di PEM AKAMIGAS Cepu - Dimas Rico Andriansyah; Ahmad Saifurriza Effasa; Hafidza Nash'ul Amrina (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2022)
With the Covid-19 pandemic, all students must adapt to the online learning environment, without meeting face to face in class. These online activities are increasingly saturated with students because learning is considered less than optimal. The purpose of this study was to find out how the impact of the Covid-19 pandemic on the learning process at PEM Akamigas Cepu. This research is a qualitative research with a descriptive approach. The samples of this research were 2 employees, 2 lecturers, and 20 students. The data analysis technique in this study is the analysis of Miles and Huberman. The impact of the Covid-19 pandemic on the learning process at PEM Akamigas Cepu caused positive and negative phenomena, namely 1) changes in the form of face-to-face learning to online learning, 2) online learning during the Covid-19 pandemic increased the use of technology in learning, and 3) online learning during the Covid-19 emergency fosters student learning independence. While the negative phenomena include 1) Learning becomes less effective and 2) The level of student understanding of the material is reduced.